Spear Prostate Biopsy 2020 (SPROB20) - Walhagen, Peter; Röbeck, Pontus; Bengtsson, Ewert; Busch, Christer; Häggman, Michael (AIDA Data Hub, 2020)
2611 scanned prostate biopsies from 460 patient cases sampled between 2015 and 2018. Annotation of clinical metadata and treatment decisions made in connection with biopsy sampling exist on case-level. Roughly 35% of the biopsies contain cancer. In-image annotations exists in macro images the form of ink markings from the clinical workflow.
Keywords: Prostate Cancer; Pathology; Medical and Health Sciences; Medicin och hälsovetenskap